Pedidikan Demokrasi dalam Pendidikan Agama Islam - Frimayanti, Ade Imelda (Lentera: Jurnal Ilmiah Kependidikan, 2015)
Democracy in the realm of education is the idea on a view of life that promotes the rights and obligations as well as equal treatment for all citizens in the process of education. In the process, the education demanded to realize dynamic developing critical and creative human beings who are able to adapt to the surrounding environment. Islamic education in a democracy is a must, because in Islam itself contains the values ââof the democratic principle it self. Islamic education puts the human position proportionally democratic nature of Islamic education here. From this democratic educational practices born intellectuals and great scholars who think freely. It is important to draw up a clear concept about the implementation of democratic education in Islamic religious education, which is implicated in the curriculum, the role of the teacher, the role of learners, learning, and evaluation of Islamic religious education.